THE ART OF BEING PASTORAL AS A MORAL THEOLOGIAN: The Importance of Gaudium et spes for the Renewal of a Tradition Raphael Gallagher, - Gallagher, Raphael (Asian Horizons, 2013)
Moral theologians are not restricted to the use of one particular method of scientific enquiry. I am working within one of the legitimate traditions, considering moral theology in terms of its practicality and pastoral application. No moral theologian, I presume, would wish to be non-pastoral. However, those who claim that being pastoral is a determinative scientific component of the science need to argue their case more cogently, less it be dismissed as merely pastoral and therefore not quite up to the standard of real theology. There is an emerging view that Gaudium et spes is the decisive conciliar locus for theological reflection on moral issues in the light of the pastoral scope of Vatican II.1 It is plausible to follow this line of thinking to clarify how we can demonstrate the art of being pastoral as a moral theologian.